2005
DOI: 10.1007/s11661-005-0052-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of interface microstructure on the strength of the transition joint between Ti-6Al-4V and stainless steel

Abstract: Solid-state diffusion bonding of Ti-6Al-4V and type 304 SS was investigated in the temperature range of 750 °C to 950 °C, under a uniaxial load for 5.4 ks in vacuum. The diffusion bonds were characterized using light and scanning electron microscopy. The scanning electron microscopic images in backscattered mode show the existence of different reaction layers in the diffusion zone. The composition of these layers was determined by energy-dispersive X-ray spectroscopy (EDS) to contain the ␣-Fe, , , FeTi, ␤-Ti, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…The linear relationship between the reaction layer thickness and time -½ suggests that the growth is a diffusion-controlled process. Taking the overall thickness of the reaction product into consideration, the relationship can be expressed by [11,22] …”
Section: Resultsmentioning
confidence: 99%
“…The linear relationship between the reaction layer thickness and time -½ suggests that the growth is a diffusion-controlled process. Taking the overall thickness of the reaction product into consideration, the relationship can be expressed by [11,22] …”
Section: Resultsmentioning
confidence: 99%
“…It could be seen through the microhardness testing that the gray and white intermetallic reaction layer had high hardness. Ghosh et al (2005) found that the intermetallic compounds had an essential influence on the mechanical properties of the joint. Thickness of intermetallic reaction layer of the joint was measured and is shown in Table 5.…”
Section: Thickness Of Intermetallic Reaction Layermentioning
confidence: 99%
“…Nickel is a strong b-stabilizing element, so migration of Ni atoms in the Ti lattice lowers the eutectoid transformation temperature of Ti and the acicular a-b Ti occurs from b-Ti owing to its decomposition during cooling. [12,19] The deep shaded diffusion area has been observed in the Ni side of both interfaces at 900°C and 950°C bonding temperatures. The width of the diffusion zone at the SS-Ni interface is smaller than that of the diffusion zone at the Ni-Ti interface.…”
Section: Resultsmentioning
confidence: 92%
“…[7][8][9] Literature reports that, at room temperature, Ti and Fe have limited solubility and promote intermetallic phases. [6,[10][11][12] Characterization of a diffusion couple of Ti-SS using transmission electron microscope study revealed the formation of reaction products such as r, v, Fe 2 Ti, FeTi, Cr 2 Ti, Fe 2 Ti 4 O, and TiC in the diffusion zone. [13] The diffusion bonding temperature has a strong influence on the formation of intermetallic phases.…”
Section: Introductionmentioning
confidence: 99%